Dampak Perubahan Kebijakan Pajak Terhadap Bisnis UMKM di Indonesia - Asep Al-Farizi Yulianto (Ikatan Cendekiawan Muda Akuntansi (ICMA), 2025)
This study aims to evaluate the impact of tax policy changes on business performance in Indonesia, particularly in the micro,small and medium enterprise (MSME) sector. Data was collected through a survey of 50 business owners located in Metro City, Lampung Province, who have directly experienced the effects of changes in tax rates and policies over the past three years. The research adopts a qualitative approach, utilizing questionnaires and limited interviews as instruments.The results of this study indicate that the majority of respondents felt the impact of tax changes, especially the increase in final income tax rates and the implementation of stricter monitoring, which led to a decrease in profit margins and an increase in administrative costs. On the other hand, some business owners recognized the benefits of tax incentives, such as tax relief for SMEs during the economic recovery period following the pandemic. This study suggests the need for a more flexible policy approach and more intensive tax education and outreach, so that business actors can respond to tax changes efficiently and maintain business sustainability.